2007
DOI: 10.4314/tjpr.v5i1.14630
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of <i>Moringa oleifera</i> Leaf Extract on Alcohol-induced Hepatotoxicity

Abstract: A study on the protective effect of Moringa oleifera leaf extract in acute alcohol-induced hepatotoxicity in rats was evaluated. Rats fed alcohol only produced significant increase in the levels of enzyme markers of tissues damage (ALT, AST and ALP), lipid peroxidation (TBARS) and decreased serum vitamin C levels compared to normal control rats. Pretreatment with

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 10 publications
2
14
0
Order By: Relevance
“…Since reduced glutathione inhibits lipid peroxidation in the liver, the decrease in GSH content in the liver could well give rise to an increase in malondialdehyde (MDA) formation, thus explaining the enhanced peroxidation in liver of ethanol-treated rats. Other factors that may contribute to a decrease in tissue-reduced glutathione include glutathione synthesis, utilization and limited intracellular reduction of oxidized glutathione to its reduced form 7 . Pre-treatment of rats with aqueous extract of Ziziphus mauritiana leaf prior to alcohol administration significantly prevented the depletion of the total antioxidant status and glutathione levels of rats compared to rats that ingested alcohol only.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since reduced glutathione inhibits lipid peroxidation in the liver, the decrease in GSH content in the liver could well give rise to an increase in malondialdehyde (MDA) formation, thus explaining the enhanced peroxidation in liver of ethanol-treated rats. Other factors that may contribute to a decrease in tissue-reduced glutathione include glutathione synthesis, utilization and limited intracellular reduction of oxidized glutathione to its reduced form 7 . Pre-treatment of rats with aqueous extract of Ziziphus mauritiana leaf prior to alcohol administration significantly prevented the depletion of the total antioxidant status and glutathione levels of rats compared to rats that ingested alcohol only.…”
Section: Discussionmentioning
confidence: 99%
“…The most important characteristic of toxic free radicals either in vivo or in vitro is peroxidation of lipids resulting in tissue damage and death of affected cells 6 . Several reports have implicated free radical-induced lipid peroxidation in the pathogenesis of alcoholinduced liver toxicity 7,8 . Antioxidants play an important role in the protection of cells and tissues against free radical-mediated tissue injury 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have indicated that excessive ethanol intake induces the mass production of free radicals in the body, which are considered to be associated with alcoholic liver disease (Ishii et al, 1997). Furthermore, a number of experimental studies demonstrated that either acute or chronic alcohol administration to experimental animals increases the formation of lipid peroxidation products, such as malondialdehyde (MDA), and decrease liver tissue levels of antioxidants, such as glutathione, ascorbic acid and antioxidant enzymes (Nadro et al, 2006;Das and Vasudevan, 2006). Despite the important progress made in understanding the pathogenesis of alcoholic liver diseases current therapies for this disease are not effective.…”
Section: Introductionmentioning
confidence: 99%
“…And also another study has showed that leaf extracts of M. oleifera had significantly restored the elevated AST, ALT and ALP enzyme levels to the normal levels [23] . Recently Nadro et al [24] has demonstrated that M. oleifera leaves protect the hepatocytes by preventing the release of these 3 enzymes. Our results are consistent with earlier studies, which strongly suggest that M. oleifera may protect the structural integrity of hepatocytes and prevent the release of cytosolic enzymes into bloodstream.Additionally, M. oleifera showed effective DPPH, hydroxyl, super oxide radical scavenging activity, suggesting that it could reduce the oxidative stress induced by chronic administration of ethanol.…”
Section: Discussionmentioning
confidence: 99%